China’s choice on the participation in establishing marine protected areas in areas beyond national jurisdiction - Yu, Minyou; Huang, Yuwen (Frontiers in Marine Science, 2023)
Currently, the issue of marine biodiversity in areas beyond national jurisdiction (ABNJ) has made a lot of significant progress in both international legislative process and national practices. As a State Party to UNCLOS, China has actively participated in the negotiations of the BBNJ agreement, in which the marine protected areas (MPAs) as one of the area-based management tools have been an issue of great concern. It is considered to be a feasible and direct conservation tool. In order to evaluate the possibility of China’s participation in the establishment of MPAs in the future, this paper analyzes the drivers for and limits on China’s involvement in the construction of MPAs in the context of the current Chinese situation. And it also puts forward possible countermeasures on how to deal with the challenges brought by the MPAs in ABNJ to China. It is concluded that there is a great possibility that China will eventually choose to participate in the establishment of MPAs in ABNJ as China advocates the concept of a maritime community with a shared future.